Together for Schoolchildren’s Health! : Arguments for Cross-border Collaboration to Promote Schoolchildren’s Health through ICT Applications in the Barents Region - Sohlman, Eiri; Kostenius, Catrine; Johansen, Ole Martin; Ryzhkova, Inna (Luleå tekniska universitet, Hälsa och rehabilitering, 2015)
Godkänd; 2015; 20150407 (andbra) ArctiChildren InNet